First evidence for temporary and permanent adhesive systems in the stalked barnacle cyprid, Octolasmis angulata - Yap, F.C.; Wong, W.L.; Maule, A.G.; Brennan, G.P.; Chong, V.C.; Lim, S.L.H. (Nature Publishing Group, 2017)
Although there have been extensive studies on the larval adhesion of acorn barnacles over the past few decades, little is known about stalked barnacles. For the first time, we describe the larval adhesive systems in the stalked barnacle, Octolasmis angulata and the findings differ from previous reports of the temporary (antennulary) and cement glands in thoracican barnacles. We have found that the temporary adhesives of cyprid are produced by the clustered temporary adhesive glands located within the mantle, instead of the specialised hypodermal glands in the second antennular segment as reported in the acorn barnacles. The temporary adhesive secretory vesicles (TASV) are released from the gland cells into the antennule via the neck extensions of the glands, and surrounded with microtubules in the attachment disc. Cement glands undergo a morphological transition as the cyprid grows. Synthesis of the permanent adhesives only occurs during the early cyprid stage, and is terminated once the cement glands reach maximum size. Evidence of the epithelial invaginations on the cement glands supports the involvement of exocytosis in the secretion of the permanent adhesives. This study provides new insight into the larval adhesives system of thoracican barnacles.